1978
DOI: 10.1080/0097840x.1978.9934991
|View full text |Cite
|
Sign up to set email alerts
|

Chronic, Intractable, Benign Pain: A Syndrome and its Treatment with Intensive Short-term Group Psychotherapy

Abstract: There is sufficient reason to classify some ongoing pain problems as syndromes. Patients who suffer with chronic, intractable, benign pain syndromes (CIBPS) have truly functional biopsychosocial disorders. There is no longer any current pathophysiology operative, and the pain syndrome persists with its psychosocially perpetuating and disrupting features. An intense group psychotherapy approach in the therapeutic milieu of a medical-surgical setting fosters and evokes affect expression and understanding. This e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

1983
1983
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 7 publications
0
11
0
2
Order By: Relevance
“…In a proportion of patients psychological or motivational factors predominate [38]. It is for this reason that Pinsky [39] has offered the descriptive term chronic benign pain syndrome. This view is based on two premises:…”
Section: Discussionmentioning
confidence: 99%
“…In a proportion of patients psychological or motivational factors predominate [38]. It is for this reason that Pinsky [39] has offered the descriptive term chronic benign pain syndrome. This view is based on two premises:…”
Section: Discussionmentioning
confidence: 99%
“…This pattern has been labelled the chronic pain syndrome. 4 Fordyce was the first to treat such patients in a behavioural setting. He argued that many of these dysfunctions could be seen as learned maladaptive behaviours and could be changed, as can any behaviour, if the contingencies of the behaviour are altered.5 He showed that by using "operant conditioning" patients' pain behaviour could indeed be abolished and their functions improved.67 Subsequent work has developed this approach, adding cognitive elements, and today most American pain clinics offer behavioural techniques.…”
Section: Treatment Of Persistent Pain Behavioural Methods Give Good Rmentioning
confidence: 99%
“…Furthermore, we believe this type of mechanism can explain all chronic pain syndromes in categories 5 and 6 of the classification in Table 1. This type of chronic pain syndrome has been described by us in the past (Pinsky, 1978(Pinsky, , 1983) as a chronic intractable benign pain syndrome (CIBPS). Descriptors of this syndrome are presented in Table 3.…”
Section: Central Neurologicalfeaturesmentioning
confidence: 99%
“…We have described the chronic intractable benign pain syndrome in earlier publications (Pinsky, 1975(Pinsky, , 1978(Pinsky, , 1983Pinsky and Crue, 1984) and include Table 3 here in order to provide clinical descriptors for this syndrome in this discussion.…”
Section: Central Psychological Featuresmentioning
confidence: 99%